Interprofessional Study Abroad: Enhancing Social Justice and Sustainability through Shared Experiential Learning. Issue 2 (3rd April 2019) - Harrison, Jennifer; Palmer, Timothy
ABSTRACT: Study abroad programs are increasingly encouraged as a method for students to develop cross-cultural competence and awareness of how to practice in diverse and multi-national settings. Barriers can exist to study abroad related to financing, scheduling, personal/professional obligations, and lack of international experience for novices. Short-term, faculty-led study abroad courses help to ameliorate these barriers, and still provide students with opportunities for experiential learning. A short-term interprofessional study course to Asia with business and health and human services undergraduate and graduate students provides opportunities for not only cross-cultural but transdisciplinary learning. The course provided participants with interprofessional learning about current issues in social justice, corporate social responsibility, development, and sustainability. Implementation, qualitative results, and future foci are discussed.